Le rose et le bleu : la fabrique du féminin et du masculin - Beauvalet-Boutouyrie, Scarlett; Berthiaud, Emmanuelle (Belin, 2016)
Une histoire de l'étude biologique, des statuts, des droits, de l'éducation, des apparences et des rôles attendus des hommes et des femmes, du XVIe au XXIe siècle, qui interroge la fabrication des concepts de masculin et de féminin.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; approches et analyses; cours; discipline; histoire; histoire et politique; postmodernisme; premier cycle; psy4910; psychologie; périodes historiques; sciences humaines; sexe/genre; stéréotypes de genre; thématiques; études de genres

Reclaiming female agency: feminist art history after postmodernism - Broude, Norma..; Garrard, Mary D.; Broude, Norma; Garrard, Mary D. (University of California Press, 2005)
This volume is the third in an influential series of anthologies by editors Norma Broude and Mary D. Garrard that challenge art history from a feminist perspective. Following their Feminism and Art History: Questioning the Litany (1982) and The Expanding Discourse: Feminism and Art History (1992), this new volume identifies female agency as a central theme of recent feminist scholarship. Framed by a lucid and stimulating critical introduction, twenty-three essays on artists and issues from the Renaissance to the present, written in the 1990s and after, offer a nuanced critique of the poststructuralist premises of 1980s feminist art history.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; post-structuralisme; postmodernisme; premier cycle; périodes historiques; thématiques